Muslim spaces and piety politics : Muslim mothers embroidering multiple interpretations of Islam in the contemporary context of transnational urban landscape of Auckland : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University, Auckland, New Zealand - Hartono, Hanny Savitri (Massey University, 2011)
New Zealand has been home to many migrants including Muslims for the past many decades. Muslims from diverse ethnic backgrounds have travelled and chosen this country as their new place of residence. Based on participant-observation fieldwork in Mt Roskill, a suburb in Auckland that is known for its highest Muslim population in New Zealand, this study seeks to map how devout Muslim mothers from different ethnicities strive to live their lives as pious Muslims. This ethnographic research aims to examine two primary issues: Muslim women’s engagement with their role as pious Muslims who endeavour to improve themselves in terms of understanding and practicing Islamic tenets in the midst of multiple discourses and practices available to them; and their engagement with their role as mothers who try to bring up their children as good Muslims in a diverse and increasingly global Muslim community within a larger scale of non-Muslim urban landscape. In particular, this study addresses how these women imbue piety in their children and improve themselves to be better Muslims in different Muslim spaces; home, tafsīr and tajwīd classes, communal prayer, their children’s madrassa and public school. Themes of music, clothing, gender-segregated spaces, greetings and ṣalāt (prayer) among others, emerged throughout the text in which piety politics is the core. For these Muslim women their lives are marked by negotiations to social mores, religious belief and practice vis-à-vis the diverse Muslim community and the larger non-Muslim context.
Keywords: Mt Roskill; Muslim women; Religious belief; Religion and parenting